Characterizing microglial gene expression in a model of secondary progressive multiple sclerosis. Issue 3 (15th November 2022) - Vainchtein, Ilia D.; Alsema, Astrid M.; Dubbelaar, Marissa L.; Grit, Corien; Vinet, Jonathan; van Weering, Hilmar R. J.; Al‐Izki, Sarah; Biagini, Giuseppe; Brouwer, Nieske; Amor, Sandra; Baker, David; Eggen, Bart J. L.; et al.
Abstract: Multiple sclerosis (MS) is the most common inflammatory, demyelinating and neurodegenerative disease of the central nervous system in young adults. Chronic‐relapsing experimental autoimmune encephalomyelitis (crEAE) in Biozzi ABH mice is an experimental model of MS. This crEAE model is characterized by an acute phase with severe neurological disability, followed by remission of disease, relapse of neurological disease and remission that eventually results in a chronic progressive phase that mimics the secondary progressive phase (SPEAE) of MS. In both MS and SPEAE, the role of microglia is poorly defined. We used a crEAE model to characterize microglia in the different phases of crEAE phases using morphometric and RNA sequencing analyses. At the initial, acute inflammation phase, microglia acquired a pro‐inflammatory phenotype. At the remission phase, expression of standard immune activation genes was decreased while expression of genes associated with lipid metabolism and tissue remodeling were increased. Chronic phase microglia partially regain inflammatory gene sets and increase expression of genes associated with proliferation. Together, the data presented here indicate that microglia obtain different features at different stages of crEAE and a particularly mixed phenotype in the chronic stage. Understanding the properties of microglia that are present at the chronic phase of EAE will help to understand the role of microglia in secondary progressive MS, to better aid the development of therapies for this phase of the disease. Main Points: Microglia switch from a pro‐inflammatory phenotype in acute EAE to a tissue remodeling phenotype in remission. Chronic EAE microglia resemble remission microglia, but show increased proliferation and regain some features of acute phase microglia.